2012
DOI: 10.1254/jphs.11226fp
|View full text |Cite
|
Sign up to set email alerts
|

Danhong Inhibits Oxidized Low-Density Lipoprotein&ndash;Induced Immune Maturation of Dentritic Cells via a Peroxisome Proliferator Activated Receptor <I>&gamma;</I>&ndash;Mediated Pathway

Abstract: Abstract. Danhong injection (DHI), a Chinese Materia Medica standardized product extracted from Radix Salviae miltiorrhizae and Flos Carthami tinctorii, is effective in the treatment of atherosclerosis (AS)-related diseases. It is widely recognized that AS is a complex inflammatory disease of the arterial wall and the dendritic cells (DCs) is a major player in the pathogenesis of AS via mediating atherosclerotic antigen presenting and T lymphocytes. Here, we determined the effect and possible mechanism of DHI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Previous studies have shown that DHI exhibited diverse pharmacological effects, including protection against vascular endothelium injury [2,3] , improvements in atherosclerosis and microcirculation [4] , and neuroprotective effects [5] . It has also been suggested that DHI might have a dose-dependent protective effect on promoting angiogenesis and mesenteric microcirculation in acute hypoxia [6,7] . In addition, an experimental study indicated that DHI had a concentration-response relationship in promoting angiogenesis potentially via the increased expression of vascular endothelial growth factor (VEGF) [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that DHI exhibited diverse pharmacological effects, including protection against vascular endothelium injury [2,3] , improvements in atherosclerosis and microcirculation [4] , and neuroprotective effects [5] . It has also been suggested that DHI might have a dose-dependent protective effect on promoting angiogenesis and mesenteric microcirculation in acute hypoxia [6,7] . In addition, an experimental study indicated that DHI had a concentration-response relationship in promoting angiogenesis potentially via the increased expression of vascular endothelial growth factor (VEGF) [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Formulated based on the TCM theory of “activating and promoting blood circulations to dissipate blood stasis and dredge collaterals” 34 , DHI has been widely used in Chinese hospitals and clinics with proven efficacy and safety 31 for treatment and prophylaxis of various cardio-cerebrovascular incidents, such as treatment of ischemia-reperfusion injury, atherosclerosis, acute coronary syndrome, hepatic veno-occlusive disease 32, 33, 43, 44 . Following our previous published work 38 showing that DHI and one of its component Danshensu serve as a direct vasodilator in normal rats, the primary finding of this study is that DHI significantly lowered BP (diastolic, systolic and mean blood pressure) in SHR compared with that of control group (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dendritic cells are important cellular elements in mediating antigen presentation and the pathogenesis of T lymphocytes in atherosclerosis. DHI can attenuate oxLDL-stimulated DC maturation by activating peroxisome proliferator activated receptors (PPAR)γ [124]. DHI increases the expression of ATP-binding cassette transporter 1 (ABCA1) levels in U937 cells stimulated by oxLDL.…”
Section: Experimental Studies and Molecular Mechanismsmentioning
confidence: 99%